RATIONALE FOR THE APPROACH TO THE MANAGEMENT OF QUALITY PRODUCTS UNDER THE ACTION OF RANDOM FACTORS DESTABILIZING THE PRODUCTION PROCESS - B. F. Bezrodny; E. A. Miheev; D. Yu. Fokin; A. S. Spirin (Научный вестник МГТУ ГА)
This article describes an approach to evaluating the effectiveness of the quality management system implementation. The approach is based on assessing the level of the probability of defect-free products production. The advantage of the approach is that it takes into account a variety of the quality management options in terms of random factors destabilizing the process of production.